Gender differences in perception of artificial intelligence-based tools - Ofosu-ampong, Kingsley (2023)
Participation of girls in Science, Technology, Engineering, and Mathematics (STEM) subjects at the higher education (HE) level continues to lag behind that of boys and consequently may affect artificial intelligence proliferation in Ghana. Numerous factors affect girls' engagement in science, one of which is the mistaken belief among girls that STEM subjects are better suited for boys. This study investigates the gender differences in AI-based tools which have become integral for teaching and learning in HE schools. Based on results from 128 students in higher education in Ghana, this article argues that gender is a significant determinant of students’ use of AI-based tools in education. The results further revealed a significant disparity in the overall levels of perceived innovation characteristics based on gender. This study urges managers of Higher Education Institutions (HEIs) to implement policies and measures aimed at facilitating women's engagement and greater familiarity with AI technologies.